Idiopathic upper extremity deep vein thrombosis: A systematic review. (19th August 2022) - Yuen, Hiu Lam Agnes; Tan, Ee; Tran, Huyen; Chunilal, Sanjeev Daya
Abstract: Background: Idiopathic upper extremity deep vein thrombosis (UEDVT) management is controversial and ranges from anticoagulation alone to the addition of further interventions such as thrombolysis and decompressive surgery. Objectives: The objective of this systematic review was to assess the effects of anticoagulation alone compared to anticoagulation with additional interventions such as thrombolysis or decompressive surgery on the incidence of recurrent UEDVT and post‐thrombotic syndrome (PTS) in patients with idiopathic UEDVT (including those associated with the oral contraceptive pill). Patients/Methods: A systematic search was conducted for studies which focused on acute UEDVT treatment defined as therapies starting within 4 weeks of symptom onset. We limited studies to those that recruited 10 or more subjects and involved at least 6 weeks to 12 months anticoagulation alone or together with additional interventions with at least 6‐month follow‐up. Primary outcomes were symptomatic recurrent radiologically confirmed UEDVT and PTS. Secondary outcomes were symptomatic venous thromboembolism, bleeding and mortality. Results: We found seven studies which reported recurrent UEDVT rates and five that reported PTS rates. All studies were retrospective or cross‐sectional. None compared anticoagulation alone to anticoagulation with additional intervention. Study heterogeneity precluded meta‐analysis and risk of bias was moderate to serious. Recurrent UEDVT occurred in 0% to 12% post‐anticoagulation alone and 0% to 23% post‐additional interventions. PTS rates varied from 4% to 32% without severe PTS. Only limited studies reported on our secondary outcomes. Conclusion: There is limited evidence behind idiopathic UEDVT management. Prospective comparative studies in this area are essential.